Navigating Complex Decisions in Restoration Investment. Issue 6 (24th November 2016) - Shoo, Luke P.; Catterall, Carla P.; Nicol, Sam; Christian, Rochelle; Rhodes, Jonathan; Atkinson, Penny; Butler, Don; Zhu, Roger; Wilson, Kerrie A.
Abstract: Ecosystem restoration requires choosing among potential interventions which differ in cost, and the time required to achieve outcomes of varying quality. Managers have different preferences for timeframes, certainty, and quality of outcomes, which can influence the choice of investment strategy. Here we develop a probabilistic approach to quantify expected restoration outcomes from alternative investment strategies, given operational constraints or alternative preferences. We apply the approach to a tropical forest restoration case study in which managers seek to allocate future resources between active planting and self‐organized regrowth. We find that the best strategy depends on the desired forest attributes and the time required for outcomes to be achieved. We quantify the trade‐off for three key forest attributes between restoring large areas of vegetation to low quality and restoring smaller areas to a higher quality. Explicit consideration of preferences and trade‐offs will enhance the likelihood that projects deliver desired outcomes.